Change management framework to support uml diagrams changes - Rajabi, Bassam Atieh; Lee, Sai Peck (Zarka Private University, 2019)
An effective change management technique is essential to keep track of changes and to ensure that software projects are implemented in the most effective way. Unified Modeling Language (UML) diagrams are widely adopted in software analysis and design. UML diagrams are divided into different perspectives in modelling a problem domain. Preserving the consistency among these diagrams is very crucial so that they can be updated continuously to reflect software changes. In this research, a change management framework is proposed to trace the dependency and to determine the effect of the change in UML diagrams incrementally after each update operation. A set of 45 change impact and traceability analysis templates for all types of change in UML diagrams elements are proposed to detect the change affected and to maintain the diagrams consistency and integrity. The proposed framework is modeled and simulated using Coloured Petri Nets (CPNs) formal language. UML is powerful in describing the static and dynamic aspects of systems, but remains semi-formal and lacks techniques for models validation and verification especially if these diagrams updated continuously. Formal specifications and mathematical foundations such as CPNs are used to automatically validate and verify the behavior of the model. A new structure is proposed for the mutual integration between UML and CPNs modeling languages to support model changes. © 2019, Zarka Private University. All rights reserved.